Optimizing HIV care by expanding the nursing role: patient and provider perspectives. - Chen, Wei-Ti; Shiu, Cheng-Shi; Simoni, Jane; Fredriksen-Goldsen, Karen; Zhang, Fujie; Zhao, Hongxin (Journal of advanced nursing, 2010)
This paper is a report of a study conducted to explore HIV healthcare services from the perspectives of both healthcare providers and patients in order to understand how to optimize HIV nursing care.
Keywords: Adult; Attitude of Health Personnel; China; Delivery of Health Care; Female; Focus Groups; HIV Infections; Hospitals, General; Hospitals, Special; Humans; Interdisciplinary Communication; Male; Medical Staff, Hospital; Nurse's Role; Nursing Staff, Hospital; Patient Satisfaction; Questionnaires